The African Entrepreneurial Ecosystem Index: Conceptual, Methodological and Empirical Flaws and the Way Forward - Wim Naudé (Institute of Labor Economics (IZA), 2024)
This paper identifies conceptual, methodological, and empirical flaws in the first African Entrepreneurial Ecosystem Index (AEEI) that was launched in 2024. These flaws limit the usefulness of the AEEI. Moreover, given that the both the notions of entrepreneurial ecosystems and composite indices are subject to subjectivity and are ad hoc, use of the AEEI can lead to simplistic policy conclusions; worse, a poorly constructed index can detract, mislead and be manipulated. It is concluded that if scholars are to embark on entrepreneurial ecosystem index building despite the concept lacking sound theoretical and empirical foundations, then it is best not to focus on the cross-country level, but to start at the sub-national level and follow best practice in composite index building. This will have the benefits of at least being more consistent with the ideas of entrepreneurship as being place dependent and that ecosystem measures should be concerned with what entrepreneurs want - and less on existing institutions.
Keywords: L26; L53; O55; O435; 330; entrepreneurship; Africa; entrepreneurial ecosystem; composite indices